Monitoring Surface Deformation Associated With Soil Erosion in Loess Plateau With an Improved Small Baseline Subset Interferometric Synthetic Aperture Radar Algorithm - Sun, Qian; Zhang, Heng; Huang, Long; He, Caihong (Frontiers in Environmental Science, 2022)
As a geomorphic process persistently occurring over the earth’s surface, soil erosion is one of the most serious environmental problems in the world nowadays, seriously threatening agriculture, natural resources, and ecosystem environments. Monitoring surface deformation associated with soil erosion will help to understand the dynamics of erosion process and the erosion mechanism. In this paper, an improved small baseline subset Interferometric Synthetic Aperture Radar (SBAS-InSAR) technique is proposed to monitor the surface deformation over the wind-water erosion crisscross region in the Loess Plateau, China by considering the internal and external environment factors in the deformation estimation model. The results show that the cumulative deformation is close to -200 mm during the investigated period. The deformation rate caused by water erosion is between -0.03-0.02 mm/mm. When the wind erosion factor changes by 1 unit, the deformation range is about -0.3-0.2 mm. It is also found that the surface deformation is highly correlated to precipitation and wind. The root mean square errors (RMSEs) of the residual deformations estimated from the proposed model are smaller than those estimated from the conventional linear and period models, demonstrating that that proposed method is more suitable to model and analyze the surface deformation in wind-water erosion crisscross region.